Monte Walsh [videorecording (DVD)] - Selleck, Tom, 1945-; Rossellini, Isabella; Carradine, Keith, 1949-; Eads, George, 1967-; Corbin, Barry, 1940-; Wincer, Simon (TNT, 2003)
Times change. Monte Walsh doesn't. For him, being a cowboy isn't a job, it's a life. And that's something the fenced-in, corporate-bean-counting ways of the onrushing 20th century must never alter.